Reconstruction of Distal Nasal Defects With a Large Postauricular Skin-Fat-Fascia Composite Graft. Issue 1 (January 2022) - He, Aijuan; Yu, Jinchao; Liu, Ninghua; Ye, Xinhai
Abstract : Background: Composite grafts have previously been reported to achieve a good outcome for nasal defect repair, but composite grafts have greater metabolic needs than simple skin. Therefore, the traditionally recommended size of a composite graft for nasal reconstruction is less than 1.5 cm in diameter. However, the distal nose is generally well supplied with blood vessels, which might support the use of larger composite grafts in such a highly vascularized recipient site. The aim of the article is to investigate whether a large skin-fat-fascia composite graft (larger than 2.0 cm) is viable for the repair of partial-thickness nasal defects. Methods: From October 2017 to December 2019, 13 patients with partial-thickness nasal defects underwent nasal reconstruction using a large postauricular skin-fat-fascia composite graft. Cases were followed up for 3 to 14 months postoperatively. The aesthetic outcome was evaluated in comparison with preoperative digital images. Results: Skin-fat-fascia composite grafts survived without graft necrosis, dermal fibrosis, or skin contraction in all cases. Favorable aesthetic outcomes were obtained in all patients, and no further revision surgery was need. Conclusions: A postauricular composite graft larger than 2.0 cm is a safe and effective reconstruction approach for partial-thickness nasal defects. This technique offers significant advantages in terms of no additional facial scar, no visible asymmetry on the face, no additional surgery for revision, and with mild scar in the donor site of the postauricular region.